VD_FINDINFO HC / 2015 / 414 vom 29. April 2015 - VD Tribunal cantonal (2015)
MESURE PROVISIONNELLE, DIVORCE, CONJOINT, MAJORITÉ{ÂGE}, ENFANT, MODIFICATIONEN GÉNÉRAL | 163 CC, 176 al. 1 ch. 1 CC, 179 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH)